The Persistence of the Italian Neo-Platonism in Counter-Reform’s Spain: Marcela’s Discourse in 'Don Quijote' and the 'Dialogues of Love' by Leone Ebreo - Matzkevich, Hernán (Escritura e Imagen, 2019)
This article highlights the traces of Neo-Platonism contained in the discourse recited by the shepherdess Marcela at the first part of Don Quijote de la Mancha. After the death of King Philip II and within the context of the Counter-Reformation, the pastoral genre offered a safe camouflage for the philosophical ideas arrived in Spain from Italy. Therefore, Marcela’s discourse offers disguised references to the intellectual links which connected Spanish writers with Neo-Platonic thinkers of the Italian Renaissance, more specifically, with Leone Ebreo’s Dialogues of Love.
Keywords: Miguel de Cervantes; Leone Ebreo; italian; Neo-Platonism; Renaissance; Spanish Golden Age; Sixteenth Century; Seventeenth Century